A BRIEF REVIEW OF MALAYSIAN BATIK DEVELOPMENTS FROM 1950s TO 1980s - Pegah Jahangiri; Sabzali Musa Kahn; Syed Alwi Syed Abubakar; Mina Hedayat (ATRAT: Jurnal Seni Rupa, 2013)
Batik Malaysia adalah proses pemberian dekorasi dan pewarnaan kain dengan menggunakan teknik lilin sebagai perintang. Industri batik di Malaysia berumur kurang dari satu abad tetapi memiliki peran sebagai identitas nasional dan terus berkembang. Artikel ini bertujuan untuk melakukan ulasan singkat tentang perkembangan batik Malaysia dari tahun 1950 hingga 1980-an. Tahun 1970-an adalah titik balik dalam produksi batik dan sebuah awal baru dalam semua hal. Dengan mengadopsi  stylus atau canting, batik dianggap memiliki nilai seni tinggi daripada sekedar kriya di Malaysia dan terkenal dengan torehan lilin dari canting dengan isen garis-garis dan titik-titik yang terampil namun rumit di atas bentuk sarung.  Kain batik tidak lagi hanya dibuat menjadi sarung di Malaysia. Terlepas dari kenyataan bahwa batik tulis populer untuk pakaian dalam dua dekade terakhir pada abad kedua puluh ini, secara keseluruhan ada penurunan keunikan dan inovasi dalam industri batik. Tampaknya ada tidak banyak minat dalam pengembangan produk baru, teknik atau strategi pemasaran baru. Desain batik juga diciptakan tanpa mengamati tren pasar. Batik Malaysia terlokalisir dan tidak terekspos pada pasar global.Kata Kunci: Malaysian Batik, Developments, Hand Drawn, Wax Resist Technique________________________________________________________________Malaysian batik as a process of decorating and dyeing fabric by using wax-resist technique is no exception. The batik industry in Malaysia is less than century old but it has a role in national identity and it keeps improving. This article aims to do a brief review on the developments of Malaysian batik from 1950s to 1980s. The 1970s were a turning point in batik production and a fresh start in all ranges. With the enthusiastic adoption of the stylus or canting, batik has become more art and less a craft in Malaysia and it is famous for its masterful but laborious canting-drawn wax lines and dots on the sarong format. Lengths of batik are no longer simply made into sarongs in Malaysia. Despite the fact that hand drawn batik was popular for tailored clothing in last two decades of twentieth century but there was an overall decrease of uniqueness and innovation in the batik industry. There seemed to be not much interest in new product development, new techniques or marketing strategies. Batik designs were also being created without looking up the market trends. Malaysian Batik was localized and it was not exposed to the global markets.Keywords: Malaysian Batik, Developments, Hand Drawn, Wax Resist Technique